'Tramline Rescue': A salvage technique for the failed elliptical excision on the leg. (22nd April 2019) - Coe, Alexander; Lyon, Matthew
Abstract: We outline an approach to achieve wound closure in the event of a failed elliptical excision on the leg. The various steps are shown, and a clinical example is presented.